Guan yu the religious afterlife of a failed hero - Haar, Barend J. ter 1958- (Oxford University Press, 2017)
Guan Yu was a minor general in the third century CE, but over time, he became known as one the most popular and influential deities of imperial China under the name Lord Guan or Emperor Guan. The work explores the cult of Guan Yu by examining the tremendous power of oral culture in creating the mythology of a deity